The review of Islamic corporate social responsibility standard and literature: future research for Malaysian Islamic banks - Mohd Sofian, Fatimah Noor Rashidah; Muhamad, Rusnah (Journal of Islamic, Social, Economics and Development (JISED), 2019)
The Malaysian government has shown strong support towards the involvement in corporate social responsibility (CSR) and the disclosure of CSR activities by the Islamic financial institutions (IFI) and the Islamic banking sector. Despite the support, there is no Islamic CSR standard established in Malaysia specifically for Islamic banks even though several CSR standards comprising conventional elements have been issued. This, therefore, evinces the need to propose an Islamic CSR guideline. Indeed, the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) has issued an Islamic CSR standard, and there is a growing amount of Islamic CSR and corporate social responsibility disclosure (CSRD) literature related to the framework. Hence, the objective of this study is to identify the current state of Islamic CSR standard and its framework, and the gaps for improvement in proposing an Islamic CSR guideline for the Malaysian Islamic banks. An analysis from the systematic literature of AAOIFI Islamic CSR standard, and Islamic CSR and CSRD literature from Web of Science and SCOPUS found that there is a need to improvise Islamic CSR guideline for the Malaysian Islamic banks due to the inconsistencies of the existing Islamic CSR frameworks in the Malaysian context.